Molecular epidemiology of rotavirus infection in Western Cameroon - Esona, M.D.; Armah, G.E.; Steele, A.D. (Journal of Tropical Pediatrics, 2003)
Rotavirus is major viral cause of diarrhoea in children worldwide. In this study, the first from Cameroon, the molecular epidemiology of rotavirus infection was investigated. Eight hundred and ninety diarrhoea stools collected from children under the age of 5 years in Western Cameroon between 1999 and 2000 were analysed for rotaviruses and further characterized by antigenic and genomic methods. Rotaviruses were detected in 21.9 per cent of stools and were highest during the cool dry season. Sixteen different electrophoretic patterns, 13 of long and three of short, were detected in the study area. The predominant subgroup detected was subgroup II (66.9 per cent) and atypical strains with long electropherotype, but subgroup I specificity were also observed. Rotavirus infection was shown to be an important component of diarrhoeal disease in young children in Cameroon. The results of this study in Cameroon reinforces the need to continue with surveillance programmes in Africa.
Keywords: Diarrhea; Africa; Cameroon; Epidemiology; Molecular; Genome; Rotavirus; Rotavirus infections; Surveillance; Medical; Atypical